Proton-exchange membrane fuel cell ionomer hydration model using finite volume method. (16th June 2022) - Van Der Linden, F.; Pahon, E.; Morando, S.; Bouquain, D.
Abstract: In this paper a dynamic membrane electrode assembly water transport model, based on the Finite Volume Method, is presented. The purpose of this paper is to provide an accessible and reproductible model capable of real time simulation. To this aim, a detailed explanation is provided regarding the equations and methods used to compute the physical-based fuel cell model. Additionally, the model is purposely developed using basic code (on Matlab™), to not be limited to a single programming language. Two phase water transport through multi-gaseous porous media (electrodes), interfacial transport, as well as diffusion, convection, and electro-osmosis within the polymer are considered. The main novelty relies in the restructuring of all equations into a single implicit system, which can iteratively be resolved through LU decomposition. This computationally efficient method allows the model to be capable of real-time simulation, by displaying the membrane water content profile evolution on a 3D figure. For nominal PEMFC operating conditions, a dry membrane reaches 35% of its final water concentration value after 2 s, and fully converges after 20 s. The final water content profile displays an 18% gradient (9 and 11 molecules per sulfonic acid sites on the anode and cathode sides, respectively). To calibrate and validate this model, mass transfer (flowmeter) and electrical (ohmmeter) methods have been applied. Highlights: Dynamic membrane electrode assembly water transport model, based on finite difference method. Water transport equations and resolution process detailed, to aim for model reproducibility. Restructuring of water transport equations into implicit equation system. Iterative equation system resolution through LU decomposition, allowing for real time simulation. 3-dimensional figures of Nafion™ hydration profile, to study its behavior.